Guiding Maxillary Left Central Incisor to Occlusion and Late Formation of a Supernumerary Tooth in the Upper Left Premolar Region - I. A. Alnaqbi; A. O. Mageet (Case Reports in Dentistry)
Hyperdontia or supernumerary teeth are the erupted or impacted teeth, which develop in addition to the regular dental series and might cause many occlusal problems. This article sheds light on a case of impacted maxillary left central incisor (21) due to a mesiodens supernumerary tooth and a late development of another supernumerary tooth in the upper left premolar area at the end of orthodontic treatment. O.A. is an 11-year, eight-month-old male, African patient presented to the orthodontic clinic with a chief complaint “My upper front tooth did not erupt although the dentist attached a wire to pull it with the help of a neighbouring tooth.” Clinically, he is medically fit and healthy, presented with class II division I malocclusion on skeletal II base; mild space discrepancy in the upper and lower dental arches; impacted 21; increased overjet; reduced overbite; localized bilateral posterior crossbite in relation to tooth number 16, 15, 25, and 26; and lower centreline shift to the left. Radiographically, lateral cephalometric radiograph confirms the skeletal relationship, whereas dental panoramic tomography (DPT) shows impacted 21 and the presence of all permanent teeth. The treatment plan consists of comprehensive orthodontic treatment using preadjusted edgewise metallic bracket, Roth prescription 0.022″×0.028″ slot and an active transpalatal arch (TPA) with palatal arms. Retention regimen comprises of upper and lower bonded retainers from canine to canine and vacuum-formed retainers (VFRs) for both dental arches.